Balanced Scorecard for decision making and development of sustainability strategies for a tourism destination - Carvajal Zambrano, Gema Viviana; Chávez López, Anabel Carolina; Nogueira Rivera, Dianelys; Velásquez Vera, Marie Lía (Journal of business and entrepreneurial studie, 2021)
The objective of this article is to use the Balanced Scorecard (BSC) for tourism management in the tourist destinations of Sucre, San Vicente, Jama and Pedernales. The development of this research was carried out by means of the analytical-exploratory method; the techniques used were the following: bibliographic review, SWOT matrix and the Balanced Scorecard Matrix. In this regard, the BSC is one of the most efficient, effective and efficient management techniques. The purpose of the BSC is to develop a management system of key factors for success, based on indicators that facilitate follow-up and achievement of objectives. Accordingly, it is concluded that the Balanced Scorecard ensures alignment between the following perspectives: Financial, Customers, TrainingInternal Processes and Environmental. In summary, the BSC will provide the study area with a complete vision for decision making for businessmen and authorities. The company's operations and measures to satisfy customers/tourists, level of innovation in processes and operational activities to improve environmental quality in the destinations in a sustainable manner, and thus improve the economy